Técnicas de Aprendizaje Automático, aplicadas en un prototipo de videojuego - Mora Parra, Alex Iván (2022)
Machine learning has currently taken great relevance in various aspects of society, this is involved in areas such as the most common as tracking preferences in social networks to more complex activities such as automated driving of vehicles, given this versatility this type of technology can be adapted to software for entertainment purposes as in the case of video games, which in turn have suffered an exponential increase in terms of development and sales in the last decade. Consequently, this research project consists of detailing the incorporation and evaluation of machine learning algorithms within a video game prototype, highlighting the various procedures related to the development of these based on agile methodologies and automated learning techniques incorporated in this type of software. The purpose of incorporating machine learning within a video game prototype is to develop an intelligent agent that is at the level of the player, which is able to process all the information collected based on the actions carried out by the player and respond in real time to these, in order to represent a behavior that reflects actions carried out by a thinking entity and thus generate an evolutionary interaction with the user.